2009
DOI: 10.1159/000232567
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Antibody Responses Induced by Subcutaneous Injection Immunotherapy with Birch and Fagales Pollen Extracts Adsorbed onto Aluminum Hydroxide

Abstract: Background: Allergen-specific subcutaneous immunotherapy (SCIT) is an antigen-specific therapy of IgE-mediated allergies. In the present study, we analyze the epitope specificities of antibody responses induced by SCIT with allergen extracts from pollen of trees belonging to the order Fagales (birch, alder, hazel) adsorbed onto aluminum hydroxide. Methods: The IgE, IgG1–4 and IgA responses to defined recombinant allergens (birch pollen: Bet v 1; alder pollen: Aln g 1; hazel pollen: Cor a 1; apple: Mal d 1) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…There is currently a clear increase in the importance of other markers, including cytokines and other mediators [24,27]. IgG antibodies against new epitopes are induced by immunotherapy [28,29] and in vitro IgG antibodies are capable of blocking mast cell and basophil mediators released during allergic reactions [30]. If we had focused our study on the most common molecules, Phl p 1, 4, 5, 6 and 2, we would have achieved a reduction in the number of profiles which would ensure that these molecules would be present when administering immunotherapy, and would therefore have achieved the therapeutic goal for most of our population.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a clear increase in the importance of other markers, including cytokines and other mediators [24,27]. IgG antibodies against new epitopes are induced by immunotherapy [28,29] and in vitro IgG antibodies are capable of blocking mast cell and basophil mediators released during allergic reactions [30]. If we had focused our study on the most common molecules, Phl p 1, 4, 5, 6 and 2, we would have achieved a reduction in the number of profiles which would ensure that these molecules would be present when administering immunotherapy, and would therefore have achieved the therapeutic goal for most of our population.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for periods of 2 years or longer was found to be more effective than the treatment for shorter periods (e.g. 1 year) [42,43]. In the case of sublingual immunotherapy, it is even necessary to administer the allergen extracts on a daily basis for long periods [44].…”
Section: Factors Limiting the Broad Application Of Allergen-specific mentioning
confidence: 99%
“…Interestingly, SIT-induced IgG antibodies do not need to recognize exactly the same epitopes as those which are recognized by IgE. In fact, it has been shown that also IgG induced against new epitopes can block IgE binding as long as these antibodies occupy parts of the IgE epitopes or cause steric inhibition of IgE binding (Pree et al 2007;Gadermaier et al 2010a). It should be also stated at this point that the ability of a ''blocking antibody'' to (Visco et al 1996;Flicker et al 2002;Jylha et al 2009;Padavattan et al 2009).…”
Section: Beneficial Role Of Allergen-specific Blocking Igg Antibodiesmentioning
confidence: 99%